Gender, alcohol and intimate partner violence: Qualitative comparative study. (October 2014) - Holmila, Marja; Beccaria, Franca; Ibanga, Akan; Graham, Kathryn; Hettige, Siri; Magri, Raquel; Munné, Myriam; Plant, Moira; Rolando, Sara; Tumwesigye, Nazarius
<x xml:space="preserve">Abstract</x> Aims: The study compares young adults' cultural understandings of intimate partner violence (IPV) and its connections with alcohol use and gender roles. Data and analyses: Comparative focus group interview data were collected in seven countries (Argentina, Finland, Italy, Nigeria, Uganda, Uruguay, Sri Lanka). Similar lists of codes and coding procedures were used in analyzing the data in all countries. Findings: According to the dominant image of IPV, the perpetrator is a man and the victim is a woman. Many discussions dealt with the gender-specific legitimation of IPV, and the groups from different countries expressed somewhat different views on the gender differences, the moral responsibility of both parties and the mitigating factors of violent behaviour in these discussions. Views on alcohol as a contributing factor for IPV were more similar in all cultures. According to most of the groups, intoxication offers a culturally acceptable excuse to escape responsibility, alcohol's pharmacological effects make violent behaviour more likely, heavy drinking can affect the relationship in a negative way, and the victim's drinking increases the risk of violence. Alcohol was said to have a somewhat different role in situational and in continuous IPV. Conclusions: Results give support to reduction of heavy use of alcohol as an available and feasible method of prevention of IPV. However, prevention of IPV requires paying attention to its other reasons as well, especially the structural gender inequality.